Desain Kolimator Neutron pada Compact Neutron Generator (CNG) untuk Boron Neutron Capture Therapy (BNCT) Menggunakan MCNP 5 - , ANGGRAENI DWI S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
leading cause of death after cardiovascular. Technology for cancer theraphy has that minimize the effect on healthy cell. It is necessary to develop the technology for cancer therapies that is Boron Neutron Capture Therapy (BNCT). The success of BNCT technology is determined by the design of collimator. Optimization of collimator design on Compact Neutron Generator (CNG) must satisfy five criteria of the International Atomic Energy Agency (IAEA) so that the neutron beam does not harm the patient. Collimator is designed with a software simulation using Monte Carlo N Particle 5 (MCNP5). The type of CNG that is used is a coaxial type with neutron yield in 1011 n/s (D-D reaction) and 1014 n/s (D-T reaction). CNG is operated at a current of 1 A and a voltage of 120 kV. The optimizations done on type of collimator material (60Ni, 9Be, 12C, BeO, 208Pb and 209Bi) and geometry of collimator (thickness and diameter). The results of the design optimization of the collimator is epithermal neutron flux of 1,34 x 10 neutron/cm s, ratio of fast neutron dose to epithermal neutron flux of 1, 62 x 10 Gycm /neutron, ratio of gamma dose to epithermal neutron flux of 99,81 x 10 Gycm / neutron, ratio of thermal neutron flux and epithermal neutron of 3,52x 10 , ratio of a neutron current to total neutron of 0,649 for the DT reaction. D-D reactions produce epithermal neutron flux of 8, 8 x 10 neutron/cm s, ratio of fast neutron dose and epithermal flux of 8,97 x 10 , ratio of gamma dose and epithermal flux of 1, 18 x 10 Gycm / neutron, thermal neutron flux ratio of the epithermal neutron of 1,89x 10 and the ratio of the neutron current and total neutron flux of 0, 46. The results of optimation can be concluded that the collimator CNG coaxial type satisfy the requirements for the DT reaction except for ratio of neutrons current and the total neutron flux. Key words : BNCT, MCNP 5, collimator, CNG, D-D reaction, D-T reaction